Establishment of a Virus-Induced Gene Silencing System in Abelmoschus manihot L. - Ting Zhang; Jiaqi Hou; Hongtao Chu; Pengyu Guo; Qianzi Sang; Zhongxu Liu; Li Cao (Plants)
Abelmoschus manihot L. (Jinhuakui, JHK) is widely cultivated for its pharmacological properties owing to its high flavonoid content and is commonly used as a garden landscape plant. However, the absence of an efficient genetic transformation system poses significant challenges for functional gene studies in this species. Virus-induced gene silencing (VIGS) is a well-established technique for exploring plant gene functions; however, this technique has not been applied to JHK. Here, a tobacco rattle virus (TRV)–VIGS system was successfully developed for the first time in JHK using the gene encoding phytoene desaturase (AmPDS) as a marker gene. This study investigated the impact of various Agrobacterium infection methods on the efficiency of AmPDS silencing. The results demonstrated that administering two injections—the first on the day of complete cotyledon expansion and the second 14 days later—using pTRV1 and pTRV2–AmPDS cultures resuspended to an OD600 of 1.0 and via the backside of the blade—led to significant photobleaching in the cotyledons 2 days after the second injection. Subsequent analyses revealed a marked reduction in both chlorophyll content and AmPDS expression. These findings suggest that a VIGS system was successfully developed in JHK, thus providing a rapid and effective method for studying gene function in this species and facilitating future research in JHK genetics.